Frutales nativos como estrategia de diversificación de yerbales y restauración productiva de la selva Paranaense - Gauna, Juan Marcelo (2023)
Misiones rainforest species provide different products such as wood, leaves or fruits. Yerba mate leaves are produced as monospecific plantations. The aim was to describe initial growth of two Campomanesia fruit-trees: guavirá and siete capotes, within yerba-mate plantations, bellow native forest and in open-field areas. Survival of guavirá during the first year after plantation was high (76 to 96%), while siete capotes had a low survival in open field areas (41%) but higher survival rates under forest and yerba-mate canopy (79%). In both species, growth depended on production system, it was maximal for guavirá in open-field areas and for siete capotes in yerba-mate plantations with minimal management.